PENGARUH DANA PIHAK KETIGA DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) PADA PERBANKAN BUMN PERIODE 2010-2019 - Dewi, Farida Citra; Zakaria, Heikal Muhammad (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
This study aims to determine the Effect of Third Party Funds and Loan to Deposit Ratio (LDR) on Return on Assets (ROA). This research was conducted at SOE Banks listed on the Indonesia Stock Exchange Period 2010-2019. This study uses multiple linear regression analysis method with a total sampling method. The results showed that: Third Party Funds had a positive and significant effect on Return on Assets (ROA). Loan to Deposit Ratio (LDR) has no significant effect on Return on Assets (ROA). Simultaneous Third Party Funds and Loan to Deposit Ratio (LDR) have a significant effect on Return on Assets (ROA).